Application of the K-Nearest Neighbor Algorithm Method to Analyze Netizen Responses and Reactions Toward the Relocation of Capital City at social media - Ziaul Haq, Muhammad; Sri Wahyuningsih, Suluh; Nursalim; Nuryanto, Uli Wildan; Rachman, Andy (SEULANGA SYSTEM PUBLISHER, 2023)
Sentiment analysis is a form of natural language processing that uses word analysis to ascertain people's thoughts, feelings, and views on a certain topic. In this study, word processing refers to the procedure used to categorize written texts into positive and negative emotion categories. Using data crawling techniques, information on public comments on the relocation of Indonesia's capital was gathered from Twitter social media. Keywords related to the move included